Highland Potsherds and Post-Sriwijaya Pottery Industry in Lampung, Indonesia - Rusyanti; Sunarningsih; Katrynada Jauharatna; Sigit Eko Prasetyo; Prahara Iqbal; Harry Octavianus Sofian; Adi Dian Setiawan; M. Fadlan S.I (SPAFA Journal)
Potsherds fragments or earthenware pottery are a type of archaeological evidence frequently discovered in surveys and excavations. These fragments represent pottery in many forms such as containers and crafts with decorated or plain surfaces. Earthen pottery has distinct characteristics and frequently represents the identity of a specific community. Sriwijaya was a famous kingdom in Sumatra from the 7th to the 10th century. Lampung is in the far south of Sumatra, and highland potsherds from this region are intriguing.  However, the highland region is arguably not the origin of these potsherds, geologically or historically. This paper examines the origin of these potsherds through granulometric analysis and ethnography. This research shows the potsherd's granulometric from the highlands is similar to the lowlands of Lampung, and they might adopt the same technique on making pottery from 1000 to 200 years ago. The development of the pottery industry changed in the last 100 years, following the implementation of the Dutch transmigration in 1905 when the Javanese potters began to produce earthen ware techniques from their homeland. The results of this study support the idea that the lowlands have been the main suppliers of pottery for the highlands and surrounding areas, from the post-Sriwijaya era until the present.